HUBUNGAN TATA RUANG KANTOR DENGAN SEMANGAT KERJA PEGAWAI DISNAKERTRANS KABUPATEN SUMEDANG - Dadang Priyatna; Lilis Komala; Norman Aditia (JRPA - Journal of Regional Public Administration, 2019)
The purpose of the research that the author did was to find out the Spatial Planning of the Office of Manpower and Transmigration, the Work Spirit of the Employees of the Manpower and Transmigration Office of Sumedang Regency, the relationship between Office Spatial Planning and the Work Spirit of the Employees at the Department of Manpower and Transmigration of Sumedang Regency. The research method used in this research is quantitative research methods, data collection techniques by conducting library research and field studies, the research sample is 33 people, the sampling technique used is probability sampling technique with the type of proportionate stratified random sampling, while the analysis technique is through percentage calculation, data normality test, and correlation test. Based on the results of research on office layout, then the data was analyzed that the office layout at the Office of Manpower and Transmigration of Sumedang Regency reached 79.89% (Good) and the morale of employees at the Department of Manpower and Transmigration of Sumedang Regency reached 78.15% (Good). From the results of the research conducted that the Office Spatial Planning and Employee Morale at the Manpower and Transmigration Service mentioned above, the authors suggest that there is still much to be improved, one of which is the arrangement of the employee's workspace so that it is more expanded so that the employees work more freely and to increase employee morale.